High-voltage DC converter for solar power station - Mohamed Qawaqzeh; Roman Zaitsev; Oleksandr Miroshnyk; Mykhailo Kirichenko; Dmytro Danylchenko; Liliia Zaitseva (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In the article the circuit design solution of DC-DC regulated resonant converter has been proposed for using with hybrid photovoltaic modules which has cooling equipment and solar concentrators in order to maximize electric power generating by such module. By using computer simulation based on multiple iterations algorithm we significantly increase the accuracy of determining the resonance circuit optimal parameters for build up DC–DC converters to work in a wide range of electric powers. Based on optimal values of the resonance LLC scheme parameters, achived by numerical calculation it can be show high values of electrical energy transformation efficiency for photovoltaic energy station equipped with high efficiency hybrid photovoltaic modules.  Implementation of microprocessor-based control into design of DC–DC back-boost converters create a new possibility to build control algorithms for increase reliability and conversion efficiency, rapid and precision stabilization of maximum power point, implementation network monitoring of photovoltaic modules, converters itself and the whole photovoltaic station parameters.